DYNAMICS OF WATER QUALITY IN TROPICAL EARTHEN FISH PONDS - NZEAGWU, A.C.; ANYANWU, E.D.; AVOAJA, D.A. (Nigerian Journal of Fisheries, 2017)
Aspects of physicochemical parameters of three fish ponds in Michael Okpara University of Agriculture, Umudike were studied between February 2015 and January 2016, to evaluate its suitability for optimum fish productivity. The results were as follows: water temperature (24.1 - 34.0 oC), depth (52.0 - 115.0 cm), transparency (30.4 - 38.2 cm), pH (6.3 - 10.8), conductivity (44.0 – 190.0 µS/cm), Total Dissolved Solids (35.1 - 98.0 mg/l), Dissolved Oxygen (3.7 - 5.1 mg/l), Biochemical Oxygen Demand (1.3 - 2.8 mg/l), nitrate (16.7 - 34.3 mg/l) and phosphate (0.01-3.33 mg/l). All the phyisco-chemical parameters evaluated were within the acceptable range set by NESREA except pH. The depth (water level) was found to be inadequate based on previous studies. In conclusion, the water quality characteristics assessed in the fish ponds were observed to be suitable for optimum fish productivity except for pH and depth (water level).